PROTOTIPE DIGITAL DESAIN KURSI BUS LISTRIK MERAH PUTIH PT. INKA MADIUN SEBAGAI SARANA TRANSPORTASI KONTINGEN G20 DI BALI (LPPM Institut Desain dan Bisnis Bali, 2024)
To be competent in the national automotive industry, PT. INKA requires innovation and product design development by utilizing Certified Independent Study Internship (MSIB) activities as an alternative to passenger seat designs. This exploration was carried out by making a prototype design to be developed as a Red and White Electric Bus (BLMP) using the Integrated Digital Design (IDD) method. Interior design exploration is one of the 9 engineering platform designs planned for this MSIB activity. Digital prototyping uses three software, namely Sketchup 2019, 3D Max 2022 and Lumion 10. Autodesk Inventor is not used because interior prototyping does not involve motion or mechanical components. The interior design that you want to show is a pleasant interior and a spacious feeling (comfort and relief). The expectation of the interior design and electric bus is maximally a gamble because as a user, it is the government that will use it as a means of transportation for the G20 2022 delegates in Bali. In this event, the government had the opportunity to show Indonesia's superiority through the work of the nation's sons and daughters in the competition for sustainable public transport. The seat model selected is in a package or module, not a single seat. This option can save space and maximize the number of passengers both sitting and standing. The seat upholstery is made thick and soft with soft materials and colors so it feels comfortable. In the insulating area between the passenger seat modules, a charging feature is also added for passengers who need power for their smartphones.